Model-Based Reorganization of Factory Structures - Lübkemann, Jens (2015)
Producing companies are facing a turbulent environment and, therefore, the reorganization of a factory becomes a continuous task. In this paper, the first part of a model-based support for the planning of a factory's organizational structure is shown. A description model consistent of different structure elements will be presented. This paper shows the first part of a description model for the reorganization of a factory.